No Difference in Transverse Abdominis Activation Ratio between Healthy and Asymptomatic Low Back Pain Patients during Therapeutic Exercise - Gorbet, Nathaniel (Hindawi Publishing Corporation, 2010)
Dysfunction of the transverse abdominis (TrA) has been associated with LBP. Several therapeutic exercises are prescribed to help target the TrA. Rehabilitative ultrasound imaging (RUSI) is used to capture activation of the TrA during exercise. The purpose was to examine TrA activation during the ADIM and quadruped exercises between healthy and nonsymptomatic LBP patients. We instructed the subjects how to perform the exercises and measured muscle thickness of the TrA at rest and during the exercises using RUSI. This allowed us to calculate TrA activation ratio during these exercises. We found no significant differences between activation ratios of the two groups during either exercise; however TrA activation during the ADIM was higher than the quadruped exercise. These exercises were capable of activating the TrA, which may be in part due to the verbal instruction they received. These exercises could be used during prevention or rehabilitation programs, since the TrA is activated.